2013
DOI: 10.1038/cddis.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1-dependent activation of Beclin 1 mediates autophagic cell death induced by sorafenib and SC-59 in hepatocellular carcinoma cells

Abstract: We investigated the molecular mechanisms underlying the effect of sorafenib and SC-59, a novel sorafenib derivative, on hepatocellular carcinoma (HCC). Sorafenib activated autophagy in a dose- and time-dependent manner in the HCC cell lines PLC5, Sk-Hep1, HepG2 and Hep3B. Sorafenib downregulated phospho-STAT3 (P-STAT3) and subsequently reduced the expression of myeloid cell leukemia-1 (Mcl-1). Inhibition of Mcl-1 by sorafenib resulted in disruption of the Beclin 1-Mcl-1 complex; however, sorafenib did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(173 citation statements)
references
References 41 publications
(52 reference statements)
9
164
0
Order By: Relevance
“…1 However, although inhibition of NFKB1 or MAPK1/3 activation enhanced ER stress-induced apoptosis, 16,63 neither of them appeared to play a part in RIPK1-mediated protection of melanoma cells, as knockdown of RIPK1 did not alter the activation levels of NFKB1 or MAPK1/3 in melanoma cells when ER stress was induced ( BECN1 that plays a crucial role in autophagosome formation is a BH3-only protein and can be in physical association with prosurvival BCL2 family proteins such as BCL2L1, BCL2, and MCL1. 37,38,64,65 This represents an important negative regulatory mechanism of BECN1-dependent autophagy. Indeed, displacement of BCL2 and BCL2L1 from BECN1 has been shown to contribute to ER stress-induced autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, although inhibition of NFKB1 or MAPK1/3 activation enhanced ER stress-induced apoptosis, 16,63 neither of them appeared to play a part in RIPK1-mediated protection of melanoma cells, as knockdown of RIPK1 did not alter the activation levels of NFKB1 or MAPK1/3 in melanoma cells when ER stress was induced ( BECN1 that plays a crucial role in autophagosome formation is a BH3-only protein and can be in physical association with prosurvival BCL2 family proteins such as BCL2L1, BCL2, and MCL1. 37,38,64,65 This represents an important negative regulatory mechanism of BECN1-dependent autophagy. Indeed, displacement of BCL2 and BCL2L1 from BECN1 has been shown to contribute to ER stress-induced autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Similarly, the other prosurvival protein MCL1 can also bind to BECN1 and disruption of the association triggers autophagy. 37,38 It seems therefore that ER stress may activate autophagy through varying mechanisms depending on cell types and stimuli in question.…”
Section: Ripk1 (Receptor [Tnfrsf]mentioning
confidence: 99%
“…Feng et al 41 showed that the biguanide metformin downregulates STAT3 activity and BCL2 expression and induces autophagy both in vitro and in vivo. A similar report by Tai and colleagues 42 showed that sorafenib, a small molecular inhibitor of KDR and PDGFRB, activates autophagy in a dose-and time-dependent manner in multiple HCC cell lines through the downregulation of phospho-STAT3 (pSTAT3) and the subsequent reduction of MCL1. Conversely, the ectopic expression of MCL1 reverses the effect of sorafenib on autophagy.…”
Section: Stat3 In Autophagymentioning
confidence: 62%
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…Sorafenib promotes autophagic death of HCC cells (17), but contrary results have also been reported (18). Activation of autophagy is involved in the resistance to cisplatin (19), whereas inhibition of autophagy enhances the effect of sorafenib (20,21) in HCC cells.…”
Section: Introductionmentioning
confidence: 93%